IMF Staff Papers, Volume 56, No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2009)
This special issue brings together world-renowned experts to provide a systematic and critical analysis of the costs and benefits of financial globalization. Contributors include Kenneth Rogoff, Maurice Obstfeld, Dani Rodrik, and Frederic S. Mishkin.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet